Optimalisasi Akuntabilitas Lingkungan Dalam Pengelolaan Ekowisata Ketapang Urban Aquaculture Dalam Konteks Good Tourism Governance (Studi Kasus Di Kabupaten Tangerang) - Eni Apriliani; Irvan Arif Kurniawan; Muhammad Yus Firdaus (Public Inspiration : Jurnal Administrasi Publik, 2025)
This study aims to determine the condition of the implementation of environmental accountability in the management of Ketapang Urban Aquaculture Ecotourism in Tangerang Regency based on the principles of Good Tourism Governance (GTG). This study was motivated by the problem of decreasing number of visitors and damage to facilities in the ecotourism area, which is considered related to the less than optimal implementation of environmental accountability. This study uses a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the implementation of environmental accountability in Ketapang Urban Aquaculture has not been fully optimal, especially in terms of increasing employment opportunities, increasing income, public health, and sustainable management of natural resources. This study is expected to be an input for local governments, tourism managers, and the community in strengthening the implementation of environmental accountability as part of the principles of Good Tourism Governance for the sustainability of ecotourism.